2020
DOI: 10.1101/2020.05.17.20104588
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

COVID 19: Real-time Forecasts of confirmed cases, active cases, and health infrastructure requirements for India and its states using the ARIMA model

Abstract: Background: COVID-19 is an emerging infectious disease which has been declared a Pandemic by the World Health Organization (WHO) on 11th March 2020. The Indian public health care system is already overstretched, and this pandemic is making things even worse. That is why forecasting cases for India is necessary to meet the future demands of the health infrastructure caused due to COVID-19. Objective: Our study forecasts the confirmed and active cases for COVID-19 until July mid, using time series Autoregressive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 12 publications
0
7
0
3
Order By: Relevance
“…The district level analysis from a study have shown that 92 districts are in red zones of the disease (Unisa et al, 2020). Mostly these red zones are found in the states Maharashtra nd Gujarat, as predicted by the ARIMA model also in study that the cases will be increasing alarmingly (Tyagi et al, 2020).…”
Section: Introductionmentioning
confidence: 68%
“…The district level analysis from a study have shown that 92 districts are in red zones of the disease (Unisa et al, 2020). Mostly these red zones are found in the states Maharashtra nd Gujarat, as predicted by the ARIMA model also in study that the cases will be increasing alarmingly (Tyagi et al, 2020).…”
Section: Introductionmentioning
confidence: 68%
“…Nonetheless, Tyagi et al . (2020) have warned that actual demand numbers can go higher than estimated healthcare infrastructures.…”
Section: Discussionmentioning
confidence: 99%
“…The estimated healthcare facilities included the numbers of beds, ICUs, and ventilators required. The required healthcare facility number calculations were following Tyagi et al . (2020).…”
Section: Methodsmentioning
confidence: 99%
“…Los modelos matemáticos son usados para entender las transiciones epidemiológicas críticas (11)(12)(13)(14), y en los últimos meses, los investigadores han venido empleando métodos matemáticos para poder pronosticar el número de casos de COVID-19 en todo el mundo. El Método Autorregresivo Integrado de Medias Móviles (ARIMA) es el que más se ha utilizado para realizar pronósticos, tal es el caso de los propuestos por Singh RK et al (11) , para Estados Unidos, España, Italia, Francia, Alemania, el Reino Unido, Turquía, Irán, China, Rusia, Brasil, Canadá, Bélgica, los Países Bajos y Suiza; por Ceylan Z (15) , para Italia, España y Francia; por Moftakhar L y Seif M (1) , para Irán; por Benvenuto D et al (16) , para Italia; por Yousaf M et al (17) , para Pakistán; por Hiteshi Tandon (18) y Rishabh Tyagi et al (19) , para India y por Perone G (20) , para Italia.…”
Section: Introductionunclassified